A computational simulation study to determine the biomechanical influence of posterior condylar offset and tibial slope in cruciate retaining total knee arthroplasty. Issue 1 (January 2018) - Kang, K-T.; Koh, Y-G.; Son, J.; Kwon, O-R.; Lee, J-S.; Kwon, S. K.
Abstract : Objectives: Posterior condylar offset (PCO) and posterior tibial slope (PTS) are critical factors in total knee arthroplasty (TKA). A computational simulation was performed to evaluate the biomechanical effect of PCO and PTS on cruciate retaining TKA. Methods: We generated a subject-specific computational model followed by the development of ± 1 mm, ± 2 mm and ± 3 mm PCO models in the posterior direction, and -3°, 0°, 3° and 6° PTS models with each of the PCO models. Using a validated finite element (FE) model, we investigated the influence of the changes in PCO and PTS on the contact stress in the patellar button and the forces on the posterior cruciate ligament (PCL), patellar tendon and quadriceps muscles under the deep knee-bend loading conditions. Results: Contact stress on the patellar button increased and decreased as PCO translated to the anterior and posterior directions, respectively. In addition, contact stress on the patellar button decreased as PTS increased. These trends were consistent in the FE models with altered PCO. Higher quadriceps muscle and patellar tendon force are required as PCO translated in the anterior direction with an equivalent flexion angle. However, as PTS increased, quadriceps muscle and patellar tendon force reduced in each PCO condition. The forces exerted on the PCL increased as PCO translated to the posterior direction and decreased as PTS increased. Conclusion: The change in PCO alternatively provided positive and negative biomechanical effects, but it led to a reduction in a negative biomechanical effect as PTS increased. Cite this article : K-T. Kang, Y-G. Koh, J. Son, O-R. Kwon, J-S. Lee, S. K. Kwon. A computational simulation study to determine the biomechanical influence of posterior condylar offset and tibial slope in cruciate retaining total knee arthroplasty. Bone Joint Res 2018;7:69–78. DOI: 10.1302/2046-3758.71.BJR-2017-0143.R1.